Respostas bioquímicas, fisiológicas e morfoagronômicas de Stylosanthes spp. sob condições de déficit hídrico - Santos, Vitor Oliveira dos (2025)
Stylosanthes Sw. is a genus that includes species considered valuable plant genetic resources due to their forage potential, high biomass production, elevated crude protein content, and tolerance to water deficit. This study aimed to evaluate the effect of drought stress on the biochemical, physiological, and morpho-agronomic responses of Stylosanthes spp. The experiment was conducted at the Horto Florestal Experimental Unit under water availability levels of 60%, 40%, and 20% of pot capacity. Two genotypes were assessed: the accession BGF 11-001 and the cultivar BRS-Bela, using a completely randomized design in a 3×2 factorial arrangement. Water deficit affected vegetative development and plant morphology, with BGF 11-001 standing out by exhibiting a higher leaf-to-stem ratio and superior forage yield.Additionally, BGF 11-001 demonstrated greater stability under severe stress conditions, maintaining higher chlorophyll content, greater accumulation of free amino acids and proline, and a significant increase in antioxidant enzyme activity, indicating effective cellular protection mechanisms and osmotic adjustment. In contrast, although BRS-Bela accumulated compatible solutes, it showed greater sensitivity to drought stress, with no increase in antioxidant activity and significant chlorophyll degradation. Bromatological and biomass analyses revealed that drought reduced biomass production and fiber content; however, BGF 11-001 maintained better forage quality under severe drought, with lower neutral detergent fiber (NDF) and acid detergent fiber (ADF) levels, and higher crude protein content. These results emphasize the importance of genotype × environment interaction and highlight the potential of the BGF 11- 001 accession as a promising candidate for breeding programs aimed at improving the adaptation of forage legumes to semiarid environments.